The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1074/jbc.m109.005959
|View full text |Cite
|
Sign up to set email alerts
|

GRK5 Deficiency Leads to Reduced Hippocampal Acetylcholine Level via Impaired Presynaptic M2/M4 Autoreceptor Desensitization

Abstract: G protein-coupled receptor kinase 5 (GRK5) deficiency has been linked recently to early Alzheimer disease (AD), but the mechanism by which GRK5 deficiency may contribute to AD pathogenesis remains elusive. Here we report that overexpression of dominant negative mutant of GRK5 (dnGRK5) in a cholinergic neuronal cell line led to decreased acetylcholine (ACh) release. This reduction was fully corrected by pertussis toxin, atropine (a nonselective muscarinic antagonist), or methoctramine (a selective M2/M4 muscari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 29 publications
2
52
0
Order By: Relevance
“…As we have recently demonstrated, selective impairment of presynaptic M2 receptor desensitization in young GRK5KO mice causes prolonged or persistent M2 signaling, which leads to reduced ACh release and cholinergic hypofunction without any evident structural degeneration (17). In aged GRK5KO animals, however, there are significant axonal defects and synaptic degenerative changes in cholinergic projection areas, such as hippocampus, piriform cortex, amygdaloid, and anterior olfactory nuclei.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…As we have recently demonstrated, selective impairment of presynaptic M2 receptor desensitization in young GRK5KO mice causes prolonged or persistent M2 signaling, which leads to reduced ACh release and cholinergic hypofunction without any evident structural degeneration (17). In aged GRK5KO animals, however, there are significant axonal defects and synaptic degenerative changes in cholinergic projection areas, such as hippocampus, piriform cortex, amygdaloid, and anterior olfactory nuclei.…”
mentioning
confidence: 90%
“…For GRK5, studies using GRK5 knock-out (GRK5KO) mice have demonstrated that one selective substrate is the family of muscarinic acetylcholine (ACh) receptors (15,16). Moreover, the selectivity of GRK5 for muscarinic ACh receptors also appears to be subtype-specific for the G i -coupled M2/M4 subtypes, rather than the G q -coupled M1 receptors (15,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The M2 muscarinic receptor is located presynapse in the hippocampus, and regulates acetylcholine release. In GRK5 knockout mice, presynaptic autoregulation by the M2 muscarinic receptor was abolished, and it caused prolonged and persistent activation (Liu et al, 2009). Furthermore, the combination of a M2 muscarinic receptor blocker and a cholinesterase inhibitor corrected β-amyloid accumulation (Cheng et al, 2010).…”
Section: Role Of Grk5 In Alzheimer's Disease and Par-kinson's Diseasementioning
confidence: 97%
“…However, the in vivo role of GRKs in D1R signaling in drug addiction remains to be determined [12,19,20] . For example, although GRK6 seems to be the most prominent GRK in both the dorsal and ventral striatum, observations in mice lacking GRK6 indicate that the D2R is its physiological target [ 21,22] .…”
Section: Attenuation Of Cocaine Cpp In Tg-s421a Micementioning
confidence: 99%